Knockdown of Dinoflagellate Condensin CcSMC4 Subunit Leads to S-Phase Impediment and Decompaction of Liquid Crystalline Chromosomes - Ting Hin Kosmo Yan; Zhihao Wu; Alvin Chun Man Kwok; Joseph Tin Yum Wong (Microorganisms, 2020)
Dinoflagellates have some of the largest genomes, and their liquid-crystalline chromosomes (LCCs) have high degrees of non-nucleosomal superhelicity with cation-mediated DNA condensation. It is currently unknown if condensins, pentameric protein complexes containing structural maintenance of chromosomes 2/4, commonly involved in eukaryotic chromosomes condensation in preparation for M phase, may be involved in the LCC structure. We find that CcSMC4p (dinoflagellate SMC4 homolog) level peaked at S/G2 phase, even though LCCs do not undergo global-decondensation for replication. Despite the differences in the chromosomal packaging system, heterologous CcSMC4p expression suppressed conditional lethality of the corresponding fission yeast mutant, suggesting conservation of some canonical condensin functions. CcSMC4p-knockdown led to sustained expression of the S-phase marker PCNAp, S-phase impediment, and distorted nuclei in the early stage of CcSMC4p depletion. Prolonged CcSMC4p-knockdown resulted in aneuploidal cells and nuclear swelling with increasing LCC decompaction–decondensation. Cumulatively, our data suggested CcSMC4p function was required for dinoflagellate S-phase progression, and we propose that condensin-mediated higher-order compaction provisioning is involved in the provision of local rigidity for the replisome.